THE RAMSEY NUMBERS OF LINEAR FOREST VERSUS 3K3 ∪ 2K4 - I W. Sudarsan; E. T. Baskoro; H. Assiyatun; S. Uttunggadewa (Journal of the Indonesian Mathematical Society, 2009)
"Pdf File"DOI : http://dx.doi.org/10.22342/jims.15.1.44.61-67